Simplifying Android Development with Coroutines and Flows: Learn How to Use Kotlin Coroutines and the Flow API to Handle Data Streams Asynchronously in Your Android App - Tigcal, Jomar (Packt Publishing, Limited, 2022)
This book is a comprehensive guide that teaches Android developers asynchronous programming using Kotlin flows and coroutines. You'll begin with the basics of asynchronous programming, including an overview of coroutines and flows, while also integrating them into your Android projects. You'll also learn how to create high-performant Android.